(untitled) (MAUSAM, 2010)
Based on the result of an experiment conducted from 1997 to 1999 during March-July, a model has been developed for relating crop coefficient of okra with time at Bangalore. The peak value of crop co-efficient was found to be 1.16 on the 9th week after sowing. On an average okra crop consumed about 547 mm of water during the growth. The mean values of crop coefficients are found to be 0.46, 1.29 and 0.66 during seedling, pod development and maturity stages respectively.